Green Tea as a Supportive Therapy for PCOS: Evaluating Its Impact on Symptom Relief - Jabłonowska, Magdalena; Grzeszczuk, Paulina (Journal of Education, Health and Sport, 2025)
Introduction: This review aims to examine the potential role of green tea in supporting the treatment of polycystic ovary syndrome (PCOS), with a focus on its impact on metabolic, hormonal and clinical symptoms associated with the condition. Materials and Methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using the following keywords: "Polycystic Ovary Syndrome", "green tea", "epigallocatechin gallate (EGCG)", "insulin resistance", "hyperandrogenism", "fertility". Summary: Polycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by hormonal imbalances, insulin resistance, and metabolic issues, leading to symptoms like irregular menstruation, hyperandrogenism, and infertility. Natural compounds, especially green tea rich in catechins like EGCG, have shown promising effects in improving insulin sensitivity, reducing androgen levels, aiding weight management, and enhancing fertility in PCOS. While preliminary studies are encouraging, further clinical research is needed to confirm the efficacy and safety of green tea and other natural therapies as complementary treatments for PCOS. Conclusions: Green tea, particularly its main catechin EGCG, shows promise in alleviating PCOS symptoms through its antioxidant, anti-inflammatory and insulin-sensitizing effects. It may help improve insulin resistance, reduce androgen levels, and support ovarian function. However, more high-quality clinical studies are needed to confirm its therapeutic potential in PCOS management.